PEMODELAN STRUKTURAL EQUATION MODEL- PARTIAL LEAST SQUARE (SEM-PLS) PADA MINAT BERTRANSAKSI MENGGUNAKAN APLIKASI OVO - Setia Ningsih; Hendra Dukalang; Armayani Arsal (Jambura Journal of Probability and Statistics, 2022)
The payment system in Indonesia is transforming from making payments in cash to non-cash. Non-cash payments can be made with various payment applications, one of which is the OVO application. Non-cash payments are less loved by many people, this is due to concerns about the security or ease and effectiveness of non-cash payment applications. Therefore, this study was conducted to analyze the factors that influence student interest in Gorontalo province in transacting using the OVO application using the Structural Equation Model Partial Least Square (SEM-PLS). The data analysis technique used is variance-based SEM. The results showed that the perceived convenience, effectiveness and security variables affected the interest in transacting using the OVO application with an R-square value of 70.70 percent.